Experimental Characterisation of the Interfacial Structure during Counter-Current Flow Limitation in a Model of the Hot Leg of a PWR - Christophe Vallée; Toshifumi Nariai; Takashi Futatsugi; Akio Tomiyama; Dirk Lucas; Michio Murase (Science and Technology of Nuclear Installations)
In order to investigate the two-phase flow behaviour during counter-current flow limitation in the hot leg of a pressurised water reactor, dedicated experiments were performed in a scaled down model of Kobe University. The experiments were performed with air and water at atmospheric pressure and room temperature. At high flow rates, CCFL occurs and the discharge of water to the reactor pressure vessel simulator is limited by the formation of slugs carrying liquid back to the steam generator. The structure of the interface was observed from the side of the channel test section using a high-speed video camera. An algorithm was developed to recognise the stratified interface in the camera frames after background subtraction. This method allows extracting the water level at any position in the image as well as performing further statistical treatments. The evolution of the interfacial structure along the horizontal part of the hot leg is shown by the visualisation of the probability distribution of the water level and analysed in function of the liquid and gas flow rates. The data achieved are useful for the analysis of the flow conditions as well as for the validation of modelling approaches like computational fluid dynamics.